2016
DOI: 10.1016/j.anbehav.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a healthy mate: sexually attractive traits as reliable indicators of current disease status in house mice

Abstract: Social interactions are critical for reproduction in many animals. Since several pathogens are transmitted by social contact, females searching for mating partners should select males that can signal being healthy. Not all signals, however, may be reliable, since males from a number of species can overcome behavioural symptoms of infection when mating opportunities are available. Here, we manipulated sickness status of male house mice, Mus musculus domesticus, by administering an immune challenge (lipopolysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 51 publications
4
46
0
Order By: Relevance
“…2d). This band recapitulated the electrophoretic behaviour of the male peripheral MUP pheromone, darcin, identified previously in male laboratory mice52 and in wild-derived domesticus from the UK3452, US5354 and Switzerland55. While a mass peak at 18893 Da, corresponding to the known mass of darcin, was evident in allopatric male domesticus samples (Fig.…”
Section: Resultssupporting
confidence: 80%
“…2d). This band recapitulated the electrophoretic behaviour of the male peripheral MUP pheromone, darcin, identified previously in male laboratory mice52 and in wild-derived domesticus from the UK3452, US5354 and Switzerland55. While a mass peak at 18893 Da, corresponding to the known mass of darcin, was evident in allopatric male domesticus samples (Fig.…”
Section: Resultssupporting
confidence: 80%
“…We found that immune-challenged animals reduced their movement as quantified by the number of times they entered and exited nest boxes, which impacted the number of different nest boxes used over night. Despite being able to detect diseased and immune-challenged conspecifics2629, mice in this study did not reduce the number of visits paid to the immune-challenged mice. Several lines of evidence indicate that urinary cues aid in the detection of diseased conspecifics in mice29.…”
Section: Discussionmentioning
confidence: 80%
“…Whether or not the responses to other infections similarly involve the VNO as well as the relative roles of other olfactory components and receptors remains to be clarified. A number of low-level infections in rodents have been shown to not only affect the quality and composition of the urine odour components, but also the quantity and extent of male scent marking [63,75]. For example, Zala et al [63] showed that wild-derived male mice infected with Salmonella enterica bacteria have both a reduced marking rate and their odours appear less attractive to females.…”
Section: (A) Mate and Partner Choice And Pathogen Avoidancementioning
confidence: 99%
“…Under natural conditions, odour and other sensory cues (e.g. ultrasonic vocalizations [75]) may result in female mice being more likely to detect and locate healthy males. Biased mating can result if the initial sensory-based choices lead to rejection of a less preferred male.…”
Section: (A) Mate and Partner Choice And Pathogen Avoidancementioning
confidence: 99%